An efficient multi-level cache system for geometrically interconnected many-core chip multiprocessor - Tirumale Ramesh; Khalid H Abed (Institute of Advanced Engineering and Science, 2022)
Many-core chip multiprocessor offers high parallel processing power for big data analytics; however, they require efficient multi-level cache and interconnection to achieve high system throughput. Using on-chip first level L1 and second level L2 per core fast private caches is expensive for large number of cores. In this paper, for moderate number of cores from 16 to 64, we present a cost and performance efficient multi-level cache system with per core L1 and last level shared bus cache on each bus line of a cost-efficient geometrically bus-based interconnection. In our approach, we extracted cache hit and miss concurrencies and applied concurrent average memory access time to more accurately determine the cache system performance. We conducted least recently used cache policy-based simulation for cache system with L1, with L1/L2, and with L1/shared bus cache. Our simulation results show that an average system throughput improvement of 2.5x can be achieved by using system with L1/shared bus cache system compared to using only first level L1 or L1/L2. Further, we show that the throughput degradation for the proposed cache system is only within 5% for a single bus fault, suggesting a good bus fault tolerance.